Small RNA methylation in Caenorhabditis elegans - Svendsen, Joshua, author; Montgomery, Taiowa A., advisor; Wilusz, Carol J., committee member; Nishimura, Erin Osborne, committee member; LaRocca, Thomas J., committee member (Colorado State University. Libraries, 2020)
Eukaryotes employ small RNAs and RNA interference (RNAi) for such diverse tasks as regulating gene expression, suppressing viral infections, and defending their genomes from foreign or parasitic sequences such as pseudogenes or transposons. In the germlines of animals, piwi-interacting RNAs (piRNAs) target and silence sequences such as these to ensure that genetic information passes from one generation to the next intact. For many animals, piRNAs must be methylated at their 3' ends to protect them from degradation, and loss of stable piRNAs results in sterility. In this study, we identify a role for piRNA methylation in maintaining germline integrity in C. elegans. We also show that methylation is important for piRNA stability in worm embryos but dispensable in the adult germline. Further, we identify additional classes of methylated small RNAs: exogenous primary short interfering RNAs (siRNAs) and a subpopulation of micro RNAs (miRNAs), as well as characterizing factors that influence which small RNAs are methylated. Finally, we provide a brief review of recent advances in the field of piRNA biology that detail the rules governing piRNA targeting and a means by which endogenous C. elegans genes avoid silencing by the piRNA-dependent RNAi pathway.
Zip file contains supplementary tables.
Keywords: germline immortality; piRNA; methylation; RNA interference; Caenorhabditis elegans; RNA